KOMPOSISI DAN KELIMPAHAN GASTROPODA DI VEGETASI MANGROVE KELURAHAN TUGUREJO, KECAMATAN TUGU, KOTA SEMARANG - Haryoardyantoro, Seto; Hartati, Retno; Widianingsih, Widianingsih (977-2407769)
Mangrove forest is one of the unique natural ecosystems with high productivity. That comes from organic detritus or litter fall which is essential nutrient sources for organism souch as fish and inverterbrates, one of which is gastropod. The purpose of this study was to determine the composition and abundance of gastropods found in mangrove vegetation Tugurejo Village, District Tugu, Semarang. This study was conducted in September 2011-March 2012. This study material is all gastropods found at the sites. Research consists of 4 stations and samples were taken with using transek (1 x 1) m2 in 3 sub stations. The research revealed that there were 11 species of gastropod belonged to 3 families, i.e. C.rithidea cingulata cingulata, Cerithidea sp.1, Cerithidea sp.2, C. quadrata, T. telescopium, Terebralia palustris (Potamididae), Littorina articulata, L. carinifera, Littorina pallescense (Littorinidae), and Sphaerassiminea miniata (Assiminidae). The species most frequently found was C. cingulata cingulata and T. telescopium. While most species rarely found is C. quadrata. The highest abundance average value was found at Station C which was dominated by Avicennia marina. The diversity index (H ') at Station A and B was low, while at Station C and D was moderate. The Uniformity Index (e) at Station A and B was low but at Station C and D was high and moderate. There was species dominance is Cerithidea cingulata cingulata at Station C.